Deciphering Electrocardiogram Of Healthy Male Ganjam Goats (Capra Hircus) (Applied Biological Research, 2018)
Electrocardiogram (ECG) of 49 healthy male goats (Capra hircus) was  recorded in three bipolar standard leads (lead I, II and III) and three  augmented unipolar limb leads (aVR, aVL and aVF). Taking the different  ECG values of all the leads into consideration, the amplitude of P wave  ranged from 0.04 mV to 0.15 mV while the P wave in the lead aVR was found  to be inverted in all the cases and the mean value was measured to be 0.1 ±  0.02 mV. The duration of P wave ranged from 0.02 to 0.06 sec. The R wave  amplitude ranged from 0.35 mV to 0.8 mV and the maximum numbers of  upright R waves were traced in lead II, III and aVF while lead I and aVL  showed inverted R wave in all the cases. The amplitude of T wave ranged  from 0.1 to 0.3 mV. The P-R interval ranged from 0.04 to 0.30 sec. The QT  interval varied between 0.18 and 0.36 sec while the R-R interval ranged  from 0.44 to 0.84 sec. The heart rate varied from 80 to 130 beats min-1.
Keywords: Augmented limb leads; bipolar limb leads; ECG; Ganjam goat